3.7(s-6)+4.6=-22

Simple and best practice solution for 3.7(s-6)+4.6=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.7(s-6)+4.6=-22 equation:


Simplifying
3.7(s + -6) + 4.6 = -22

Reorder the terms:
3.7(-6 + s) + 4.6 = -22
(-6 * 3.7 + s * 3.7) + 4.6 = -22
(-22.2 + 3.7s) + 4.6 = -22

Reorder the terms:
-22.2 + 4.6 + 3.7s = -22

Combine like terms: -22.2 + 4.6 = -17.6
-17.6 + 3.7s = -22

Solving
-17.6 + 3.7s = -22

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '17.6' to each side of the equation.
-17.6 + 17.6 + 3.7s = -22 + 17.6

Combine like terms: -17.6 + 17.6 = 0.0
0.0 + 3.7s = -22 + 17.6
3.7s = -22 + 17.6

Combine like terms: -22 + 17.6 = -4.4
3.7s = -4.4

Divide each side by '3.7'.
s = -1.189189189

Simplifying
s = -1.189189189

See similar equations:

| 3x^2+17x-10=0 | | 9+x/4=10 | | 20.00-1.45v=1.15 | | 8u^2-36u-20=0 | | X-18=65 | | 16=n/2 | | 28=4x-2(-x+4) | | 16=n/2 | | 3.14*6*6*5= | | (-27)-12= | | (35X^2-11X-8)/(5X+2) | | 6x+7=-9 | | 3nx^8-6nx^4-45n=0 | | 7k^2-14k=-7 | | (x^2)+14x+24=0 | | -8=-4x-2(x-11) | | 3.14*5*5*12= | | (2r+8)=88 | | (2r+8)=88 | | 2x+2(x-3)=30 | | 90xX=45 | | X^2-38x+4=0 | | x^9-27=0 | | -8+(-11)= | | 5m^2-7m-2= | | -48x-34=60 | | x+90=45 | | 7x^3-28x-35x=0 | | 12^8/35t^6 | | 5x^2+11x+38=0 | | -5(-8)= | | 3.14*5*5*7= |

Equations solver categories